OPTIMALISASI DESAIN SURVEI SEISMIK BERDASARKAN DATA EVALUASI TEKNIS DAN PARAMETER YANG TERSEDIA DALAM SOFTWARE MESA - Fadhil, Muhammad; Sota, Ibrahim; Siregar, Simon Sadok (Jurnal Fisika FLUX, 2016)
ABSTRACT. Seismic data acquisition is done to get a recording of seismic data. The quality of seismic data judged from a comparison between the amount of reflection signals received by signal interference received. Three-dimensional seismic survey (3D) provides an overview of the subsurface geology accuracy better than seismic two- dimensional (2D). Seismic three-dimensional (3D) generally require a higher cost than the two-dimensional (2D) because the density of the firing point and the receivers more. Making  the  seismic  survey  design  into  a  solution  of  a  problem  before  conducting seismic exploration for exploration which was preceded by design rarely meet with failure and have a positive impact in optimizing the configuration of the spread as well as aspects of the economy. Of the four designs seismic surveys that have been made and the discussions it was found that all the firing patterns, to the desired target has been able to meet the desired targets. Firing patterns have value slanted fold better than firing patterns orthogonal, brick, and the patch because it has a value greater fold. Firing patterns patch is firing patterns are more suitable for shallow penetration compared with the three other designs, but in terms of the cost will be more expensive. Of the four firing patterns that have been made can be concluded that the firing patterns of brick is more objective in terms of both data and the distribution of funds will be issued. KEYWORDS: seismic, seismic survey design, firing patterns